Knowledge and Practices of the Kankanaey of Palina Kibungan, Benguet on Indigenous Knowledge Systems in Mitigating Climate Change - Wandalen, Rhe-Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the knowledge and practices of the Kankanaey residents of Palina, Kibungan, Benguet regarding Indigenous Knowledge Systems (IKS) in mitigating climate change. Anchored on environmental governance and the interrelationship between indigenous knowledge and climate action, the study focused on four domains: agriculture, environment, socio-cultural, and social. A quantitative descriptive survey design was used, supplemented by interviews, focus group discussions, and site observations. The respondents were 94 Kankanaey residents representing the youth, elders, barangay officials, teachers, farmers, and women. Data were gathered using a researcher-made questionnaire validated through pretesting, with a reliability result of .812. Statistical tools included frequency, proportion, weighted mean, ANOVA, paired sample t-test, and Pearson product-moment correlation. Findings revealed that respondents were moderately knowledgeable in agricultural, environmental, and socio-cultural IKS, and fully knowledgeable in the social IKS. In terms of practice, agricultural IKS was slightly practiced, environmental and socio-cultural IKS were moderately practiced, and social IKS was fully practiced. Significant differences were found in the level of knowledge across agriculture, environment, and socio-cultural domains, while no significant difference was found in the social domain. No significant differences were found in the extent of practice across all domains. A significant positive relationship was established between knowledge and practice, indicating that greater knowledge of IKS is associated with stronger application. The study supports SDG 13, SDG 15, SDG 11, SDG 4, and SDG 17 by promoting climate action, environmental protection, community resilience, education, and partnership-based governance. Its sustainability impact lies in strengthening cultural preservation, indigenous governance, environmental stewardship, and community-based climate resilience.
Keywords: Climate Action; Community Resilience; Environmental Governance; Indigenous Knowledge Systems; Kankanaey; Palina; Sustainable Agriculture; Traditional Practices; Indigenous Leadership